2015
DOI: 10.1017/s0305000915000550
|View full text |Cite
|
Sign up to set email alerts
|

Low-income fathers’ speech to toddlers during book reading versus toy play

Abstract: Fathers’ child-directed speech across two contexts was examined. Father–child dyads from sixty-nine low-income families were videotaped interacting during book reading and toy play when children were 2;0. Fathers used more diverse vocabulary and asked more questions during book reading while their mean length of utterance was longer during toy play. Variation in these specific characteristics of fathers’ speech that differed across contexts was also positively associated with child vocabulary skill measured on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…Further, Liszkowski and Tomasello (2011) only found a relation based on a dichotomized measures of parent and infant pointing. Previous studies have found evidence that the context influences parents language and gesture use (Puccini, Hassemer, Salomo, & Liszkowski, 2010;Salo, Rowe, Leech, & Cabrera, 2015), however the differences in findings across these studies could be driven by a variety of factors including sample size, age range of the infants, and/or methodology and more work is need to parse apart the various factors that might influence the relation between parents' and infants' pointing. We did find a trend in the relations between mothers' pointing and their infants' pointing when examined at the level of communicative intent.…”
Section: Relations Between Parent and Infant Pointingmentioning
confidence: 99%
“…Further, Liszkowski and Tomasello (2011) only found a relation based on a dichotomized measures of parent and infant pointing. Previous studies have found evidence that the context influences parents language and gesture use (Puccini, Hassemer, Salomo, & Liszkowski, 2010;Salo, Rowe, Leech, & Cabrera, 2015), however the differences in findings across these studies could be driven by a variety of factors including sample size, age range of the infants, and/or methodology and more work is need to parse apart the various factors that might influence the relation between parents' and infants' pointing. We did find a trend in the relations between mothers' pointing and their infants' pointing when examined at the level of communicative intent.…”
Section: Relations Between Parent and Infant Pointingmentioning
confidence: 99%
“…Lastly, parent-child book reading also represents a positive learning opportunity by providing occasions for learning new words within a stimulating context (Mol et al, 2008; Farrant and Zubrick, 2013; Salo et al, 2016). A meta-analysis conducted by Mol et al (2008) identified an association of moderate effect size between dialogic book reading and expressive vocabulary, as well as an association of small effect size with receptive vocabulary.…”
Section: Introductionmentioning
confidence: 99%
“…For example, picture books contain more unique words than child-directed speech (Hayes & Ahrens, 1988; Massaro, 2015; Montag, Jones, & Smith, 2015), and this lexical diversity does indeed seem to become a part of the spoken language input during book reading. Recordings of caregivers and children interacting in book reading contexts suggest that picture book reading provides children with more speech input and more lexically sophisticated speech than other caregiver-child activities (Crain-Thoreson, Dahlin, & Powell, 2001; Salo, Rowe, Leech, & Cabrera, 2016; Sosa, 2016; Weizman & Snow, 2001). These findings suggest that one means by which picture book reading may contribute to language outcomes is by exposing children to words that they might not otherwise encounter or might encounter less frequently.…”
mentioning
confidence: 99%